2017
DOI: 10.1038/s41598-017-04695-5
|View full text |Cite
|
Sign up to set email alerts
|

The gastropod shell has been co-opted to kill parasitic nematodes

Abstract: Exoskeletons have evolved 18 times independently over 550 MYA and are essential for the success of the Gastropoda. The gastropod shell shows a vast array of different sizes, shapes and structures, and is made of conchiolin and calcium carbonate, which provides protection from predators and extreme environmental conditions. Here, I report that the gastropod shell has another function and has been co-opted as a defense system to encase and kill parasitic nematodes. Upon infection, cells on the inner layer of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 28 publications
2
51
0
Order By: Relevance
“…Snails are often infected by helminth parasites (Bayne, ). The gastropod shell provides little defense against helminth infections, although a few striking examples have shown that the shell can successfully kill nematode parasites (Rae, ; Williams & Rae, ). For example, there are probably tens of thousands of species of trematodes (Trematoda: Digenea), the vast majority of which utilizing gastropods as obligatory hosts in their life cycles (van der Knaap & Loker, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Snails are often infected by helminth parasites (Bayne, ). The gastropod shell provides little defense against helminth infections, although a few striking examples have shown that the shell can successfully kill nematode parasites (Rae, ; Williams & Rae, ). For example, there are probably tens of thousands of species of trematodes (Trematoda: Digenea), the vast majority of which utilizing gastropods as obligatory hosts in their life cycles (van der Knaap & Loker, ).…”
Section: Introductionmentioning
confidence: 99%
“…Snails are often infected by helminth parasites (Bayne, 1983). The gastropod shell provides little defense against helminth infections, although a few striking examples have shown that the shell can successfully kill nematode parasites (Rae, 2017;Williams & Rae, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They also contain small amounts of protein. The shells consist of calcium carbonate crystals organized within a matrix of protein thus making GAS shells as an effective absorber [16].…”
Section: Introductionmentioning
confidence: 99%
“…Snails such as Achatina fulica (Williams and Rae, 2015) and Cepaea nemoralis (Williams and Rae, 2016) can actively trap, encase and kill nematodes using their shell. This whole process is remarkably efficient at killing nematodes, often hundreds at a time and is evolutionary conserved across the phylogeny of the Stylommatophora (terrestrial slugs and snails) (Rae, 2017b). An exciting opportunity has indirectly arisen from this research that 4 may allow us to actually track the evolution of nematodes at the molecular level over time.…”
mentioning
confidence: 99%
“…An exciting opportunity has indirectly arisen from this research that 4 may allow us to actually track the evolution of nematodes at the molecular level over time. Snail shells that are hundreds of years old present in museums have been shown to have nematode encased in their shells (Rae, 2017b(Rae, , 2018. As nematode DNA can be extracted from shells this may facilitate genomic analysis over time using these preserved 'fossilised' specimens.…”
mentioning
confidence: 99%